Analisis Supply dan Demand Campuran Aspal Panas (Hot Mix) di Provinsi Lampung - Rahayu Sulistyorini (Balitbangda Provinsi Lampung, 2016)
With an increasing need for asphalt about 3.53% annually demand and supply conditions in Lampung Province will not in balanced for some years in the future. Purpose of this research is to study on the increased need for hot asphalt in Lampung Province next few years for a national road project the Ministry of Public Works and Highways provincial road projects of Dinas Bina Marga Lampung Province. While the purpose of this research is the availability of the results of a needs analysis of hot asphalt in Lampung and strategic recommendations to overcome the increase in the future. The percentage of hotmix increasing need in 2014 and 2015 on the project and the National Roads Provincial Roads is 30%. The results of the analysis of needs and the availability of hot mix in 2014 showed that the needs on the ground and the availability of Lampung is still balanced. The results of the analysis of needs and the availability of hot mix in 2015 showed the need for maximum hot mix at the span of the last 5 months AMP production capacity that exceeds the average - average per month. The differences are considerable between the need and availability of hot mix and amounted to 2 times as much and AMP are available are not able to make ends meet in 2018. Asphalt Mixing Plant (AMP) unit in Lampung Province can actually meet the needs hotmix in Lampung Province in 2018 on the assumption of production per year. Hotmix job execution patterns are always held on the last 6 months within the work calendar , making the maximum hotmix requests per month that exceeds the production capacity in AMP per month. This is a problem on AMP s inability to meet all demand maximum hotmix the last 6 months for the next few years. Increased production of hot mix in Asphalt Mixing Plant to be a temporary solution would be difficult to do because of the increasing need Unit Asphalt Mixing Plant ( AMP ), which operates in the province of Lampung is now being used for decades / old. Changes in the pattern of implementation of the work hotmix by service providers who carry out work hotmix at a span of 6 months in a year needs to be done so that the distribution of hot mix into each project can be uneven road annually.